Multidrug resistant strains of Escherichia coli from Faeces of Layer birds in Jamalpur, Bangladesh - Aminatu Abubakar Sani, Usman Bashir Usman, Hauwa'u Umar Mungadi (Sokoto Journal of Medical Laboratory Science)
Escherichia coli (E. coli) is a facultative anaerobic bacterium commonly found in the intestines and is mostly harmless. However, E. coli has the ability to cause a wide range of diseases in the gastrointestinal, urinary, and nervous systems of man and animals. Indiscriminate use of antibiotics in animal production, hospitals, and agriculture are among the major sources for the development of antimicrobial resistance. Through horizontal gene transfer, E. coli possesses a number of resistance genes that have made it resistant to many antibiotics. The aim of this study was to detect E. coli and determine the antimicrobial resistant pattern of E. coli isolated from poultry faecal samples from Jamalpur, Bangladesh. The antibiotic susceptibility pattern was assessed using disc diffusion method according to the guidelines of the Clinical and Laboratory Standards Institute and the detection was achieved using the polymerase chain reaction